Biomechanical risk factors for rotator cuff syndrome in high-risk occupations: A prospective study protocol - Angelica E. Lang; Kenzie B. Friesen; Josh Lawson; Prosanta Mondal; Niels Koehncke; Soo Y. Kim; Philip Chilibeck (PLoS ONE, 2025)
Background Rotator cuff syndrome (RCS) is the most common upper limb musculoskeletal disorder worldwide. RCS negatively impacts quality of life and comes with high costs to the individual and society through time loss of work or healthcare usage. Identifying modifiable risk factors for RCS is a critical avenue for exploration to improve prevention and treatment of RCS. Objective The overarching goal of this research is to explore the connection between shoulder kinematics and RCS in high-risk occupations and determine if pre-injury shoulder kinematics during a standardized overhead reaching motion are a risk factor for symptomatic RCS. Methods A prospective cohort design will be used to assess 292 individuals who work in high-risk occupations, such as construction, farming, and healthcare. Workers without any shoulder pain or disorders will be asked to attend an in-laboratory baseline testing session. First participants will complete questionnaires about their baseline symptoms, personal characteristics, and work exposures. They will then perform a standardized functional reaching task while their shoulder movement is tracked with optical motion capture. Participants will be surveyed every 3 months for two years; individuals with any indications of shoulder symptoms that develop during the study period will be further assessed with clinical impingement tests. Logistic regression and survival analyses will be performed to determine if scapular kinematics pre-injury, combined with several individual and work-related factors, are a risk factor for development of RCS. Proposed Results These findings will provide empirical evidence to clarify the contribution of biomechanics to injury development. Specifically, it is expected that scapular kinematics at the baseline assessment will be a risk factor for the development of RCS. Conclusions This research represents a crucial step for understanding shoulder musculoskeletal health. This information is foundational for development of innovative, evidence-based treatment and prevention strategies.